Detection of Real Time QRS Complex Using Wavelet Transform - Fatima Yasmeen; Mohammad Arifuddin Mallick; Yusuf Uzzaman Khan (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents a novel method for QRS detection. To accomplish this task ECG signal was first filtered by using a third order Savitzky Golay filter. The filtered ECG signal was then preprocessed by a Wavelet based denoising in a real-time fashion to minimize the undefined noise level. R-peak was then detected from denoised signal after wavelet denoising. Windowing mechanism was also applied for finding any missing R-peaks. All the 48 records have been used to test the proposed method. During this testing, 99.97% sensitivity and 99.99% positive predictivity is obtained for QRS complex detection.